ANALISIS PENGARUH TINGKAT PROFITABILITAS, KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN - Dian Indriyani; Tina Sulistiyani (Universitas Ahmad Dahlan, 2013)
This research was aimed to examine the influence of profitability level, investment decision, funding decision and dividend policy towards company value in companies affiliated in Jakarta Islamic Index (JII) listed in Indonesian Stock Exchange. Population and also research samples was companies that their stocks included in Jakarta Islamic Index (JII) calculation listed in Indonesian Stock Exchange of 2010-2012 periode that had a complete financial statement stated in Rupiah and paying dividend routinely during the research period numbered 6 companies. Dependent variables used i.e. company value (DPR) while its independent variable was profitability level (ROE), investment decision (PER), funding decision (DER) and dividend policy (DPR). This research used a panel data regression test device and classical assumption test. The independent variable influence testing towards dependent variable was performed partially through a statistical t-test. Based on the research result partially using a statistical t-test showed that profitability level, investment decision and dividend policy significantly influenced company value.